Empirical Realities of Teacher-Child Interaction and Cognitive Development of Pre-Primary School Children In Ibadan, Oyo State - Rosemary Nmadinobi Ikie; Moses Dele Amosun; Iyanuoluwa Emmanuel Olalowo (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The characteristics of teacher-child interaction play a paramount role in the cognitive development of children. Despite its significance, literature abounds on how these characteristics, such as teachers' actions, words, gestures, and responsibilities, may improve or deter children’s development (Grosse, 2022; Bartholo et al., 2022). Thus, this study was carried out to contribute to the body of knowledge, particularly taking into account preschools from a developing nation such as Nigeria. It sought to establish the extent and influence of teacher-child interaction on the cognitive development of pre-primary children in the Ibadan metropolis. The study employed a correlational survey design. A multi-stage approach was used for sampling and sampling. The total sample size for the study was 200, which comprised 50 pre-primary class teachers and 150 pre-primary school children. Two research questions were raised and answered. Teacher-Child Interaction Observation Schedule (TCIOS) = 0.72, Child Cognitive Development Rating Scale (CCDRaS) = 0.79, and Questionnaire on Teacher’s Perception of Teacher-Child Interaction on Cognitive Development (QTPTCICD) = 0.80 were the instruments used for the study. Data collected were analysed using descriptive statistics and Pearson Product Moment Correlation. The result of the findings revealed that the extent of teacher-child interaction and level of cognitive development was great with = 3.41and = 3.61, respectively, as well as the teachers' perceived influence on teacher-child interaction on cognitive development, was positive ( = 3.16). Although the finding showed no significant relationship between teacher-child interaction and cognitive development (r=0.01; p>0.05), it is recommended that teachers, however, should maintain the positive, quality interaction that characterizes preschool teaching, which may resonate with other uniqueness and educational needs of the child.